ANALISIS LINGKUNGAN KERJA DAN SENIORITAS TERHADAP KINERJA SERTA PRODUKTIVITAS KARYAWAN PADA PERUSAHAAN - nilam purwaningtyas; Anita Kartika Sari (Universitas Linggabuana PGRI Sukabumi, 2022)
This research was made based on stories and direct observations by the author. This research and analysis aims and has the intention to find out how conditions in the world of work and seniority that occur can affect employee performance and comfort. Conditions in the world of work are often interesting to discuss. Often, seniority behavior still occurs in some workplaces that are carried out by colleagues. The research entitled